IDENTIFICATION OF TYPE, INTENSITY AND PREVALENCE OF VANAME SHRIMP (Litopenaeus vannamei) ECTOPARASITES IN TRADITIONAL POND CULTURE - Juliana Juliana; Yuniarti Koniyo (Journal of Fish Health, 2022)
The production of vannamei shrimp (Litopenaeus vannamei) continues to decline due to parasitic attacks on ponds in North Gorontalo Regency. Ectoparasites are one of the factors that can cause failure in the cultivation of vannamei shrimp (Litopenaeus vannamei). This study aims to determine the type of ectoparasites, intensity, and prevalence of vannamei shrimp cultured in traditional ponds in the North Gorontalo Regency. A sampling of the research was carried out at five research stations. This research was selected randomly in 5 plots of ponds, and the total number of shrimp was as many as 150 tails. At each station, samples were taken of 30 vannamei shrimp (Litopenaeus vannamei). Sampling using fishing gear in the form of nets. The observed models were 8-10 cm in size alive. Observations of ectoparasites were carried out microscopically using a Zeis Binocular microscope with 10x magnification. Data analysis used descriptive analysis of ectoparasites, intensity, and prevalence of ectoparasites found. The study's results found four types of ectoparasites found in vannamei shrimp: Zoothanium sp, Epistylis sp, Carchesium sp, and Vorticella sp. The intensity of ectoparasite attack on shrimp was categorized as low to moderate infection, namely 4-7 individuals/head. The prevalence rate is 80-100%, with moderate to very severe disease.